Electrical resistance material, current detection resistor, and method for manufacturing electrical resistance material

A chromium-aluminum mixture with controlled mass ratios and resistance temperature coefficients addresses high resistance and power loss issues, enabling low-resistance, stable resistors for current detection in electric vehicles.

JP7606844B2Active Publication Date: 2024-12-26KOA CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020168415
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-05
Publication Date
2024-12-26
Estimated Expiration
2040-10-05

AI Technical Summary

Technical Problem

Existing chromium-aluminum alloys used for resistors result in high resistance values and significant power loss, making them unsuitable for current detection in electric vehicles.

Method used

A mixture of aluminum and chromium in a non-chemically bonded state, with specific mass ratios and resistance temperature coefficients, is used to create a resistor with low resistance values and stable resistance to temperature changes.

Benefits of technology

The solution reduces volume resistivity and power loss, enabling precise resistor formation with low temperature coefficient of resistance, suitable for current detection in electric vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606844000002
    Figure 0007606844000002
  • Figure 0007606844000003
    Figure 0007606844000003
  • Figure 0007606844000004
    Figure 0007606844000004
Patent Text Reader

Abstract

To provide an electric resistance material capable of forming a resistor with a low resistance value, a resistor for current detection, and a manufacturing method of the electric resistance material.SOLUTION: An electric resistance material 10 is made of a mixture 12 containing aluminum and chromium. The electric resistance material 10 has a chromium content of 7 [mass%] or more and 13 [mass%] or less based on the total mass of the mixture 12, and a temperature coefficient of resistance of -150 [ppm / °C] or more and +100 [ppm / °C] or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrically resistive material, a current sensing resistor, and a method for producing an electrically resistive material. [Background technology]

[0002] Patent Document 1 discloses a chromium-aluminum alloy. This chromium-aluminum alloy has a composition in which the content of aluminum in chromium is in the range of 10 to 50% by weight, and the volume resistivity is 500 μΩ·cm or more. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 62-77436 Summary of the Invention [Problem to be solved by the invention]

[0004] When a resistor is manufactured using this chromium-aluminum alloy as an electrical resistance material, the resistor has a high resistance value.

[0005] When such resistors are used in resistors for current detection, the power loss in the resistor becomes large, making them unsuitable as electrical resistance materials for current detection resistors.

[0006] SUMMARY OF THE PRESENT DISCLOSURE An object of the present invention is to provide an electrical resistance material capable of forming a resistor with a low resistance value, a current detection resistor, and a method for manufacturing the electrical resistance material. [Means for solving the problem]

[0007] According to one embodiment of the present invention, there is provided an electrical resistance material comprising a mixture containing aluminum and chromium, the mixture being in a dispersed state in which the aluminum and the chromium are not chemically bonded to each other, and the content of the chromium is 7% by mass or more and 13% by mass or less based on the total mass of the mixture, The aluminum content is 87% by mass or more and 93% by mass or less based on the total mass of the mixture, The temperature coefficient of resistance is between -150 ppm / ℃ and +100 ppm / ℃. Effect of the Invention

[0008] According to this embodiment, the chromium content is set to 7% by mass or more and 13% by mass or less, so that the volume resistivity of the electrical resistance material can be reduced, and thus, by using this electrical resistance material, it is possible to form a resistor with a low resistance value.

[0009] By using this resistor, a resistor with a low resistance value can be formed, making it possible to suppress power loss in the resistor. For this reason, this electrical resistance material is suitable as a material for resistors for current detection.

[0010] Furthermore, by forming such a resistance material into a mixture, the temperature coefficient of resistance can be kept within the range of -150 ppm / °C to +100 ppm / °C. Therefore, compared to electrical resistance materials whose resistance value changes significantly with temperature changes, this electrical resistance material is more suitable as a material for resistors for current detection. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a diagram showing the structure of a mixture constituting a resistive material according to an embodiment. [Diagram 2] FIG. 2 is a diagram showing each step of the method for producing an electrical resistance material according to an embodiment. [Diagram 3] FIG. 3 is a diagram showing the relationship between the chromium content and the volume resistivity (ρ) in the mixture. [Figure 4] FIG. 4 is a diagram showing the relationship between the chromium content in the mixture and the temperature coefficient of resistance (TCR). [Diagram 5] FIG. 5 is a diagram showing a structure of a first comparative example. [Figure 6] FIG. 6 is a diagram showing a structure of a second comparative example. [Figure 7] FIG. 7 is a diagram showing the relationship between the heat treatment temperature applied in the heat treatment step and the volume resistivity (ρ). [Figure 8] FIG. 8 is a diagram showing the relationship between the heat treatment temperature applied in the heat treatment process and the temperature coefficient of resistance (TCR). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In recent years, exhaust gas regulations have been strengthened in many countries in order to address environmental issues, and the development of electric vehicles (EVs) has progressed.

[0013] In electric vehicles, weight reduction is required to extend the distance that can be traveled on a single charge, and the materials constituting electric vehicle parts are being replaced with aluminum. Parts used in electric vehicles include battery electrodes and electric wires, and replacement of the material of the battery electrodes and the material of the electric wires with aluminum is being considered.

[0014] In addition, electric vehicles use shunt resistors, which are resistors for detecting current, and the inventors came up with the idea of ​​making the resistors lighter by constructing them from an electrical resistance material mainly made of aluminum.

[0015] However, few aluminum-based electrical resistance materials have been developed, and there are no electrical resistance materials that have both a low resistance value and a low temperature coefficient of resistance.

[0016] Therefore, we have developed an electrical resistance material that is mainly made of aluminum and has a low volume resistivity. It is preferable that the electrical resistance material to be developed has a lower temperature coefficient of resistance than ordinary electrical resistance materials.

[0017] Hereinafter, embodiments of the present invention will be described, but the manufacturing method of the electric resistance material, the electric resistance material, and the resistor using the electric resistance material shown in the embodiments are not limited to shunt resistors used in electric vehicles, and can be used for general resistors. Furthermore, the electric resistance material described in the following embodiments may be used as a material for other parts.

[0018] [Electrical resistance materials] The current detection resistor according to the embodiment includes a resistor element made of an electric resistance material and a terminal electrically connected to the resistor element.

[0019] The electrical resistance material forming the resistor is composed of a mixture of aluminum (Al) and chromium (Cr).

[0020] The mixture has a chromium content of 7% by mass or more and 13% by mass or less, based on the total mass of the mixture, which is 100% by mass. The mixture also has an aluminum content of 87% by mass or more and 93% by mass or less, based on the total mass of the mixture. This allows the resistor to be made lighter.

[0021] It is preferable that the mixture does not contain impurities other than aluminum and chromium, but it may contain unavoidable impurities of 1.0% by mass or less based on the total mass of the mixture. The content of the unavoidable impurities is preferably 0.1% by mass or less, and more preferably 0.01% by mass or less.

[0022] Even if the mixture contains impurities, the aluminum content is adjusted to be within the range of 87% by mass to 93% by mass. In other words, the total aluminum content including impurities is adjusted to be 87% by mass to 93% by mass.

[0023] Furthermore, the mixture achieves a temperature coefficient of resistance of −150 ppm / ° C. or more and +100 ppm / ° C. or less at the above-mentioned chromium content.

[0024] The temperature coefficient of resistance is calculated based on the rate of change of resistance and the amount of temperature change. For example, when a mixture that shows a first resistance value R1 at a first temperature T1 changes to a second resistance value R2 when the mixture is changed to a second temperature T2, the temperature coefficient of resistance TCR [ppm / °C] is calculated by the following formula:

[0025] TCR={(R2-R1) / R1} / {(T2-T1)×1000000}

[0026] The electrical resistance material composed of the mixture is in a dispersed state in which the aluminum and chromium are not chemically bonded to each other, that is, the metal particles remain in particulate form and are uniformly dispersed.

[0027] An example of the state in which aluminum and chromium are chemically bonded is a state in which aluminum and chromium are chemically bonded to form a compound. Also, an example of the state in which aluminum and chromium are chemically bonded is a state in which aluminum and an element other than chromium are bonded to form a compound. Furthermore, an example of the state in which aluminum and chromium are chemically bonded is a state in which chromium and an element other than aluminum are bonded to form a compound.

[0028] Therefore, no compounds are formed in the electrically resistive material composed of the mixture, and the electrically resistive material does not contain compounds of aluminum and chromium.

[0029] Here, the electrical resistance material composed of the mixture is preferably in a dispersed state in which aluminum and chromium are not chemically bonded, but may include a state in which aluminum and chromium are chemically bonded, so long as the temperature coefficient of resistance and volume resistivity are not affected. Also, the electrical resistance material is preferably in a state in which it does not have a compound, but may include a compound of aluminum and chromium, so long as the temperature coefficient of resistance and volume resistivity are not affected.

[0030] Strictly speaking, the electrical resistance material made of the mixture may contain a compound formed by chemically bonding aluminum and chromium, so long as it does not affect the temperature coefficient of resistance and the volume resistivity. Also, the electrical resistance material made of the mixture may contain a compound formed by bonding aluminum with an element other than chromium, so long as it does not affect the temperature coefficient of resistance and the volume resistivity. Also, the electrical resistance material may contain a compound formed by bonding chromium with an element other than aluminum, so long as it does not affect the temperature coefficient of resistance and the volume resistivity.

[0031] These compounds may be contained alone or in combination in the electrical resistance material, and the total content of the compounds contained in the electrical resistance material is 1.0 [mass %] or less based on the total mass of the electrical resistance material. Preferably, the total content of the compounds contained in the electrical resistance material is 0.1 [mass %] or less based on the total mass of the electrical resistance material, and more preferably, the total content of the compounds is 0.01 [mass %] or less.

[0032] Here, each compound contained in the electrical resistance material constitutes a part or all of the unavoidable impurities contained in the electrical resistance material.

[0033] The electrical resistance material composed of the mixture has a volume resistivity of 17 [μΩ·cm] or more and 50 [μΩ·cm] or less.

[0034] When chromium is dissolved in aluminum, the amount of chromium dissolved in aluminum is limited to about 0.7% by mass. Therefore, when forming an electrical resistance material by dissolving chromium in aluminum, it is difficult to set the volume resistivity of the electrical resistance material to between 17 μΩ·cm and 50 μΩ·cm.

[0035] Therefore, in this embodiment, the electrical resistance material is made of a mixture containing aluminum and chromium, so that the volume resistivity of the electrical resistance material is set to 17 [μΩ·cm] or more and 50 [μΩ·cm] or less.

[0036] Here, the volume resistivity refers to the electrical resistance value of a cube having a side of a unit length of a substance, and in this embodiment, the unit is [μΩ·cm].

[0037] The electrical resistance material is in the form of a film. Examples of the film include a thick film, a thin film, and an ultra-thin film. The electrical resistance material of the present embodiment is in the form of a thin film having a thickness of less than 10 μm, preferably 3 μm or less and 0.1 μm or more.

[0038] The lower limit of the thickness of this electrical resistance material is determined by the components that make up the electrical resistance material.

[0039] In this embodiment, a film-like electrical resistance material is taken as an example for explanation, but the shape of the electrical resistance material is not limited to this.

[0040] For example, in another embodiment, the electrical resistance material is bulk-shaped. The term "bulk-shaped" refers to a thick shape. One example of the bulk-shaped electrical resistance material is an electrical resistance material having a thickness of 100 [μm] or more, and preferably, the thickness of the electrical resistance material is 200 [μm] or more and 4000 [μm] or more.

[0041] The upper limit of the thickness dimension of this electrical resistance material can be, for example, equal to or less than the outer dimension of the electrical resistance material.

[0042] (Structure of Resistance Material) 1 is a diagram showing the structure of a mixture 12 constituting an electrical resistance material 10 according to this embodiment. The mixture 12 is composed of aluminum particles 14 made of aluminum and chromium particles 16 made of chromium.

[0043] The mixture 12 is different from the state where chromium is dissolved in aluminum. In the mixture 12, adjacent aluminum particles 14 and chromium particles 16 are arranged in close contact with each other.

[0044] The aluminum particles 14 have an average particle size of 100 nm or less, and the chromium particles 16 have an average particle size of 100 nm or less.

[0045] The mixture 12 is in a dispersed state 18 in which the aluminum in the aluminum particles 14 and the chromium in the chromium particles 16 are not chemically bonded to each other. As a result, the mixture 12 does not contain any compound in which aluminum and chromium are bonded to each other.

[0046] Here, "not containing a compound in which aluminum and chromium are combined" means that the content of the compound is 1.0% by mass or less, based on the total mass of the electrical resistance material composed of the mixture.

[0047] [Effects of electrical resistance materials] The electrical resistance material 10 of this embodiment is an electrical resistance material 10 made of a mixture 12 containing aluminum and chromium. The electrical resistance material 10 has a chromium content of 7 [mass %] or more and 13 [mass %] or less, based on the total mass of the mixture 12, and has a temperature coefficient of resistance of -150 [ppm / °C] or more and +100 [ppm / °C] or less.

[0048] According to this configuration, the electrical resistance material 10 is made of the mixture 12 having a chromium content of 7 mass % or more and 13 mass % or less, thereby making it possible to reduce the volume resistivity (ρ) of the electrical resistance material 10. As a result, by using this electrical resistance material 10, it becomes possible to form a resistor with a low resistance value.

[0049] A resistor having a low resistance value can be formed by using a resistor made of the electrical resistance material 10. This makes it possible to suppress power loss in the resistor, making the electrical resistance material 10 an electrical resistance material suitable for use in resistors for current detection.

[0050] Moreover, the mixture 12 has a temperature coefficient of resistance (TCR) of -150 [ppm / °C] to +100 [ppm / °C], and has a smaller change in resistance value with respect to temperature change than a general electrical resistance material. Therefore, the mixture 12 is more suitable as a material for a resistor for current detection than electrical resistance materials whose resistance value changes greatly with temperature change.

[0051] Moreover, the electrical resistance material 10 of this embodiment is in a dispersed state 18 in which aluminum and chromium are not chemically bonded to each other. Furthermore, the electrical resistance material 10 of this embodiment does not contain any compound of aluminum and chromium.

[0052] According to this configuration, aluminum and chromium can be uniformly dispersed in the electrical resistance material 10, improving resistance characteristics such as the temperature coefficient of resistance (TCR). In addition, since the variation in size of the components of the electrical resistance material 10 can be suppressed, it becomes possible to stably set the volume resistivity (ρ).

[0053] Moreover, the electrical resistance material 10 of this embodiment has a volume resistivity (ρ) of 17 [μΩ·cm] or more and 50 [μΩ·cm] or less.

[0054] According to this configuration, it is easier to suppress power loss in the resistor, compared to a case in which a resistor is formed using an electrical resistance material 10 having a volume resistivity (ρ) of more than 50 [μΩ·cm] as a resistor element.

[0055] In addition, compared to a case where a resistor is formed using an electrical resistance material 10 with a volume resistivity (ρ) of less than 17 [μΩ·cm] as a resistor, the boundary between the resistor and the terminal can be made clearer, which makes it easier to perform tasks such as adjusting the width dimension of the resistor to set the resistance value.

[0056] Furthermore, the electrical resistance material 10 of the present embodiment is in the form of a film, and a resistor can be formed in the form of a film. This allows a resistor to be formed from a film-like resistor, thereby enabling the resistor to have high precision.

[0057] Here, the electrical resistance material 10 shown as another embodiment is in a bulk state with a thickness dimension of 100 μm or more. In this case, by forming a resistor from a bulk resistive body, it is possible to increase the allowable current of the resistor.

[0058] The resistor of this embodiment uses the electrical resistance material 10 as a resistive element. This makes it possible to provide a resistor with low power loss and a small temperature coefficient of resistance (TCR). Therefore, a resistor made of the electrical resistance material 10 can be used for current detection.

[0059] [Method of manufacturing electrical resistance materials] Next, an example of a method for producing the above-mentioned electrical resistance material 10 will be described with reference to the drawings.

[0060] 2 is a diagram showing the steps of the method for producing an electrical resistance material according to the embodiment. As shown in FIG. 2, the method for producing an electrical resistance material 10 includes a preparation step P1 for preparing to form a mixture 12, a mixture film-forming step P2 for forming the mixture 12, and a heat treatment step P3 for performing a heat treatment on the mixture 12 thus formed.

[0061] In the mixture film-forming process P2, a sputtering method is used as a method for forming the mixture 12 that constitutes the electrical resistance material 10. The sputtering method is a method for forming a film-like mixture 12 on a substrate by alternately irradiating the substrate with aluminum and chromium.

[0062] (preparation process) In the preparation process P1, an aluminum film-forming material and a chromium film-forming material that will be sputtering targets are manufactured. As a manufacturing method for the aluminum film-forming material and the chromium film-forming material, for example, a sintering method is used in which raw material powder is heated at a temperature below the melting point to solidify the raw material powder and form each film-forming material.

[0063] In addition, when an aluminum ingot for film formation and a chromium ingot for film formation are available, this preparation step P1 can be omitted.

[0064] (Mixture film formation process) In the mixture film forming step P2, the mixture 12 is formed by a sputtering method.

[0065] In this mixture film-forming process P2, sputtering is performed using an aluminum film-forming material, and then sputtering is performed using a chromium film-forming material.

[0066] First, the aluminum film forming material formed in the preparation step P1 is placed on one side of a vacuum chamber, and a substrate is placed on the other side of the vacuum chamber. Next, argon gas (Ar) is introduced into the vacuum chamber.

[0067] Then, the aluminum film forming material is used as a cathode and the substrate is used as an anode, and a high voltage is applied to the anode and cathode, with the power applied to the anode and cathode being 130 W or more and 160 W or less.

[0068] This ionizes the argon gas, and the ionized argon gas is collided with the aluminum coating material at high speed. Aluminum particles are ejected from the aluminum coating material by this collision and adhere to the substrate.

[0069] Next, the aluminum film forming material arranged on one side of the vacuum chamber is replaced with the chromium film forming material formed in the preparation step P1, and argon gas (Ar) is introduced into the vacuum chamber.

[0070] Then, a high voltage is applied to the chromium film forming material as the cathode and the substrate as the anode, and the power applied to the anode and cathode is set to 1 W or more and 20 W or less.

[0071] This ionizes the argon gas, and the ionized argon gas is collided with the chromium film-forming material at high speed. Chromium particles are ejected from the chromium film-forming material by this collision and adhere to the substrate. Through the above steps, a mixture 12 containing aluminum particles and chromium particles is formed on the surface of the substrate.

[0072] The conditions for the sputtering performed in this mixture film formation process P2 are as follows: a gas flow rate of argon gas in the vacuum chamber is 10 [sccm] or more and 30 [sccm] or less, a gas pressure is 0.25 [Pa] or more and 0.45 [Pa] or less, and a holding time is 40 [min] or more and 80 [min] or less.

[0073] The retention time is adjusted so that the thickness dimension of the mixture 12 formed on the substrate becomes a required thickness.

[0074] In addition, the DC power applied to the chromium film forming material is set based on the chromium content contained in the mixture 12, within the range of 1 W or more and 20 W or less, and the retention time is set according to the chromium content and film thickness.

[0075] By performing sputtering under these conditions, the chromium content in the mixture formed on the base material is set to 7 [mass %] or more and 13 [mass %] or less.

[0076] In this way, by forming the mixture 12 by sputtering, it is possible to form the mixture 12 in a dispersion state 18 in which the aluminum and chromium are dispersed more or less uniformly, as compared to the case where a melting method is used in which the raw materials are melted and shaped.

[0077] In order to uniformly disperse chromium in aluminum, the chromium particles must be small. Therefore, the average particle size of the chromium particles 16 constituting the mixture 12 is set to 100 nm or less. Preferably, the average particle size of the aluminum particles 14 constituting the mixture 12 is set to 100 nm or less.

[0078] In addition, since the mixture 12 is formed by sputtering, it is possible to suppress the formation of compounds of aluminum and chromium. Preferably, the mixture 12 is prevented from forming compounds of aluminum and chromium.

[0079] (Heat treatment process) In the heat treatment step P3, the mixture 12 formed in the mixture film forming step P2 is heat-treated to stabilize the mixture 12.

[0080] In the heat treatment step P3, the mixture formed in the mixture film forming step P2 is subjected to a heat treatment in a nitrogen atmosphere at 150° C. or more and 250° C. or less for approximately 60 minutes.

[0081] The heat treatment is preferably carried out in a nitrogen atmosphere.

[0082] The temperature condition for this heat treatment is preferably 150° C. or higher and 250° C. or lower.

[0083] [Effects of the manufacturing method for electrical resistance materials] In the manufacturing method of the electrical resistance material 10 of this embodiment, a mixture 12 containing aluminum and chromium and having a chromium content of 7 mass % to 13 mass % is formed by sputtering. Then, the temperature applied to the mixture 12 in the process after the formation is set to 250° C. or less.

[0084] In this way, by forming the electrical resistance material 10 from the mixture 12 having a chromium content of 7 mass % or more and 13 mass % or less, it is possible to reduce the volume resistivity (ρ) of the electrical resistance material 10. As a result, by using this electrical resistance material 10, it is possible to form a resistor with a low resistance value.

[0085] Furthermore, by forming the mixture 12 by sputtering and setting the temperature to which the mixture 12 is applied in the process after the formation to 250° C. or less, it is possible to suppress the formation of compounds between aluminum and chromium.

[0086] This allows aluminum and chromium to be uniformly dispersed in the resulting electrical resistance material 10. Also, it becomes possible to suppress variation in size of components of the electrical resistance material 10.

[0087] Furthermore, it becomes possible to stabilize the volume resistivity (ρ), which is determined according to the chromium content, and to reduce the temperature coefficient of resistance (TCR).

[0088] A resistor having a low resistance value and a small temperature coefficient of resistance (TCR) can be formed by using this electrical resistance material 10. Therefore, it is possible to manufacture the electrical resistance material 10 suitable for use as a material for resistors for current detection.

[0089] The method for producing the electrical resistance material 10 of this embodiment also includes a heat treatment step P3, in which the mixture 12 thus formed is heat treated at 150° C. or higher.

[0090] This makes it possible to improve the moldability of the mixture by heat treatment, as compared with the case where the heat treatment is carried out at a temperature of less than 150°C.

[0091] Furthermore, in the method for producing the electrical resistance material 10 of this embodiment, the heat treatment step P3 is performed in a nitrogen atmosphere at 250° C. or less for about 60 minutes.

[0092] [Other embodiments] Although the embodiments of the present invention have been described above, the above-mentioned embodiments merely illustrate some of the application examples of the present invention, and are not intended to limit the technical scope of the present invention to the specific configurations of the above-mentioned embodiments.

[0093] In the present embodiment, the case where sputtering is performed using an aluminum film-forming material and then using a chromium film-forming material has been described as an example, but the present invention is not limited to this.

[0094] For example, sputtering may be performed using a chromium film forming material, followed by sputtering using an aluminum film forming material. Alternatively, sputtering may be performed using both an aluminum film forming material and a chromium film forming material at the same time. In this case, the DC power applied to the aluminum film forming material and the DC power applied to the chromium film forming material are set to different magnitudes depending on the chromium content.

[0095] In addition, in this embodiment, a sputtering method is used as a method for producing the electrical resistance material 10 at a temperature of 250°C or less while uniformly dispersing aluminum and chromium, but this is not limited to this method.

[0096] Other methods for producing the electrical resistance material 10 include, for example, a vapor deposition method in which the electrical resistance material 10 is formed by vapor deposition, a cold spray method, or a low-temperature firing method.

[0097] Moreover, the electrical resistance material 10 is formed in a film shape by a sputtering method, but the present invention is not limited to this.

[0098] For example, a method is available in which fine powder consisting of aluminum particles 14 and chromium particles 16 with an average particle size of 5 μm or less is produced in a state where the powder is rapidly cooled, such as by water atomization, and the powder is used by a cold spray method to form the film-like electrical resistance material 10. Another method is available in which the film-like electrical resistance material 10 is formed by a low-temperature sintering process. EXAMPLES

[0099] The electrical resistance material according to the embodiment of the present invention was prepared, and the temperature coefficient of resistance (TCR) and volume resistivity (ρ) of the prepared electrical resistance material were measured. The method of preparing a specimen and the method of evaluating the specimen will be described below.

[0100] [Preparation of specimen] <Preparation of electrical resistance materials> - Preparation of specimen 1

[0101] First, in a preparation step, an aluminum film-forming material and a chromium film-forming material that will become sputtering targets are produced.

[0102] In this preparation process, 99.9% pure aluminum (Al) manufactured by Kojundo Chemical Laboratory Co., Ltd. is heated to a temperature below 660.3°C, the melting point of aluminum, and solidified to form an aluminum film material.

[0103] In addition, 99.9% pure chromium (Cr) powder manufactured by High Purity Chemical Laboratory Co., Ltd. is heated to a temperature below 1907.0°C, the melting point of chromium, to solidify the raw material and form a chromium film material.

[0104] Next, in the mixture film forming step, the mixture 12 is formed by the sputtering method shown in the embodiment. The conditions for sputtering performed in this mixture film forming step are as follows.

[0105] Discharge gas: Argon gas Gas flow rate: 20 [sccm] Gas pressure: 0.35 [Pa] ·DC power: Al 145[W] Cr 5.5[W] Retention time: approx. 60 minutes

[0106] The unit of gas flow rate, [sccm], is an abbreviation for "Standard Cubic Centimeter per Minute" and indicates the volume of fluid flowing per hour under standard conditions of 1 [atmosphere] and 0 [°C].

[0107] In this way, the electrical resistance material of specimen 1 was obtained.

[0108] -Preparation of specimen 2 The electrical resistance material of specimen 2 was obtained by carrying out the same process as specimen 1, except that the DC power applied to the chromium film-forming material was set to 6 [W].

[0109] -Preparation of specimen 3 The electrical resistance material of specimen 3 was obtained by carrying out the same process as specimen 1, except that the DC power applied to the chromium film-forming material was set to 7 [W].

[0110] - Preparation of specimen 4 The electrical resistance material of specimen 4 was obtained by carrying out the same process as specimen 1, except that the DC power applied to the chromium film-forming material was set to 7.5 [W].

[0111] - Preparation of specimen 5 A resistive material for Specimen 5 was obtained by performing the same processes as those for Specimen 1, except that the DC power applied to the film-forming material for chromium was set to 8 [W].

[0112] · Preparation of Specimen 6 A resistive material for Specimen 6 was obtained by performing the same processes as those for Specimen 1, except that the DC power applied to the film-forming material for chromium was set to 9 [W].

[0113] · Preparation of Specimen 7 A resistive material for Specimen 7 was obtained by performing the same processes as those for Specimen 1, except that the DC power applied to the film-forming material for chromium was set to 15 [W].

[0114] · Preparation of Specimen 8 A resistive material for Specimen 8 was obtained by performing the same processes as those for Specimen 1, except that the DC power applied to the film-forming material for chromium was set to 17 [W].

[0115] · Preparation of Specimen 9 A resistive material for Specimen 9 was obtained by performing the same processes as those for Specimen 1, except that the DC power applied to the film-forming material for chromium was set to 20 [W].

[0116] [Evaluation of Specimens] [Measurement of Chromium Content in the Mixture] For the measurement of the chromium content in the mixture, "JSM-7900F" manufactured by JEOL Ltd. was used.

[0117] [Measurement of Resistance Value and Volume Resistivity (ρ)]

[0118] For the measurement of the resistance value and the volume resistivity (ρ), "Semiconductor Device Parameter Analyzer B1500A" manufactured by KEYSIGHT was used, and the volume resistivity (ρ) was measured under the condition that the ambient temperature was 25 [°C].

[0119] [Measurement of TCR] For the calculation of the temperature coefficient of resistance (TCR), the resistance value measured at 25 [°C] and the resistance value measured at 100 [°C] were used.

[0120] [Evaluation Results] Table 1 shows the measurement results of the temperature coefficient of resistance (TCR) and volume resistivity (ρ) of the electrical resistance material of each specimen.

[0121] [Table 1]

[0122] Fig. 3 is a diagram showing the relationship between the chromium (Cr) content and the volume resistivity (ρ) in the mixture, and the measurement results in Table 1 are shown by dots in Fig. 3. Fig. 4 is a diagram showing the relationship between the chromium content and the temperature coefficient of resistance (TCR) in the mixture, and the measurement results in Table 1 are shown by dots in Fig. 4.

[0123] According to the results in Table 1 and FIG. 3, the volume resistivity (ρ) of the mixture 12 increases as the chromium (Cr) content increases, so that the volume resistivity is roughly proportional to the chromium (Cr) content.

[0124] Here, the electrical resistance material 10 in this embodiment is used in a resistor for detecting current. Therefore, in order to suppress power loss in the resistor, the electrical resistance material 10 is required to have a volume resistivity (ρ) of 50 [μΩ·cm] or less.

[0125] Accordingly, based on the measurement results, the chromium (Cr) content in the mixture 12 constituting the electrical resistance material 10 is set to 13 mass % or less.

[0126] The resistor of the resistor made of the electrical resistance material 10 is electrically connected to the electrodes. Here, as an example, it is necessary to clarify the boundary between the resistor and the electrodes in order to adjust the shape of the resistor to set the resistance value. For this reason, it is required that the volume resistivity of the resistor is ten times or more the volume resistivity of the electrodes.

[0127] The volume resistivity of an electrode made of a general material is 1.7 [μΩ·cm] at room temperature, and the volume resistivity of the electrical resistance material 10 must be 17.0 [μΩ·cm] or more.

[0128] Therefore, based on the measurement results, the chromium (Cr) content of the mixture 12 constituting the electrical resistance material 10 is set to 7 [mass %] or more.

[0129] 4, the temperature coefficient of resistance (TCR) of the mixture 12 exceeds +100 ppm / °C when the chromium (Cr) content is less than 7 mass %, and the temperature coefficient of resistance (TCR) of the mixture 12 becomes less than -150 ppm / °C when the chromium (Cr) content exceeds 13 mass %.

[0130] In this way, by setting the chromium (Cr) content of the mixture 12 to be equal to or greater than 7 [mass%] and equal to or less than 13 [mass%], the temperature coefficient of resistance (TCR) can be set to be equal to or greater than -150 [ppm / °C] and equal to or less than +100 [ppm / °C].

[0131] [Heat treatment test] Next, among the specimens obtained as described above, specimen 5, which showed good values ​​for both the temperature coefficient of resistivity (TCR) and the volume resistivity (ρ), was further subjected to heat treatment and the changes in the temperature coefficient of resistivity (TCR) and the volume resistivity (ρ) were observed.

[0132] <Heat treatment> Specimen 5 was subjected to heat treatment under the following conditions.

[0133] Under nitrogen atmosphere Heating rate: 150[℃ / min] Heat treatment time: Leave for 60 minutes after reaching the target temperature

[0134] <Heat measurement in heat treatment test>

[0135] <Measurement of heat treatment temperature> The temperature setting for the heat treatment was performed using an "Infrared Rapid Lamp Annealing System RTA-4000" manufactured by ULVAC Vacuum Riko Co., Ltd. In addition, the resistance value and volume resistivity (ρ) were measured using a "Semiconductor Device Parameter Analyzer B1500A" manufactured by KEYSIGHT Corporation, and the volume resistivity (ρ) of the mixture 12 after the heat treatment was measured under the condition of an ambient temperature of 25°C.

[0136] [Heat treatment test results] The results of the heat treatment tests are shown below.

[0137] In the heat treatment of the heat treatment step P3, when the temperature applied to the mixture 12 exceeds 300° C., a compound (Al7Cr) of aluminum (Al) and chromium (Cr) starts to form.

[0138] Fig. 5 is a diagram showing the structure of a first comparative example 30, and Fig. 6 is a diagram showing the structure of a second comparative example 32. Figs. 5 and 6 show compound formation states 20 and 22 in which compounds are formed in a mixture 12 heated to over 300°C.

[0139] The mixture 12 of each of Comparative Examples 30 and 32 contains aluminum particles 14 made of aluminum and chromium particles 16 made of chromium. In each of Comparative Examples 30 and 32, the average particle size of the aluminum particles 14 is 100 nm or less, and the average particle size of the chromium particles 16 is 100 nm or less.

[0140] In the mixture 12 of each of the comparative examples 30 and 32, compounds (Al7Cr) 34 and 36 in which aluminum (Al) constituting the aluminum particles 14 and chromium (Cr) constituting the chromium particles 16 are chemically bonded are formed.

[0141] In the mixture 12 of each of Comparative Examples 30 and 32, the adjacent aluminum particles 14, chromium particles 16, and compounds 34, 36 are arranged in close contact with each other.

[0142] The average particle size of the compound 34 of the first comparative example 30 is larger than the average particle size of the aluminum particles 14 and the chromium particles 16, and the outer dimension of the maximum part exceeds 100 [nm].

[0143] Compound 36 of second comparative example 32 is formed in a dendritic shape. The average particle size of compound 36 is larger than the average particle size of aluminum particles 14 and chromium particles 16, and the outer dimension of the maximum part exceeds 100 [nm].

[0144] In each of Comparative Examples 30 and 32, the dispersion state of aluminum and chromium becomes non-uniform, and resistance characteristics such as temperature coefficient of resistance (TCR) are significantly deteriorated. Therefore, in order to obtain good resistance characteristics, the temperature condition of the heat treatment needs to be 300°C or less.

[0145] FIG. 7 is a diagram showing the relationship between the heat treatment temperature applied in the heat treatment process and the volume resistivity (ρ), and shows the measurement results of the volume resistivity (ρ) of mixture 12 versus the temperature when mixture 12 having a chromium (Cr) content of 7.3 [mass %] was heat treated.

[0146] From the measurement results shown in FIG. 7, if the mixture 12 is heat-treated at 250°C or less, the fluctuation in the volume resistivity (ρ) can be suppressed, and the volume resistivity (ρ) can be set to approximately the set value (18.7 μΩ cm) determined based on the chromium (Cr) content.

[0147] On the other hand, when the mixture 12 is heat-treated at 250°C or higher, the volume resistivity (ρ) deviates from the set value (18.7 μΩ·cm) determined based on the chromium (Cr) content. Furthermore, when the mixture 12 is heat-treated at 300°C or higher, the volume resistivity (ρ) significantly deviates from the set value (18.7 μΩ·cm).

[0148] Here, when the mixture 12 is heat-treated at 300°C or higher, the formation of a compound between aluminum and chromium begins. In the compound formation states 20 and 22 in which compounds are formed in the mixture 12, electron scattering is reduced compared to the dispersion state 18 in which aluminum and chromium are uniformly dispersed. Then, the resistance value decreases and the temperature coefficient of resistance (TCR) increases.

[0149] Fig. 8 is a diagram showing the relationship between the heat treatment temperature applied in the heat treatment process and the temperature coefficient of resistance (TCR). Fig. 8 shows the measurement results of the temperature coefficient of resistance (TCR) of the mixture 12 with a chromium (Cr) content of 7.3 [mass %] being heat treated for 60 minutes versus the heat treatment temperature.

[0150] From the measurement results shown in FIG. 8, when the mixture 12 is heat-treated at 250° C. or less, the temperature coefficient of resistance (TCR) is within ±10 ppm / ° C., and when the mixture 12 is heat-treated at 250° C. or less, the temperature coefficient of resistance (TCR) can be suppressed to within ±100 ppm / ° C.

[0151] On the other hand, if the mixture 12 is heat-treated at 300° C. or higher, the temperature coefficient of resistance (TCR) exceeds ±1000 ppm / ° C.

[0152] From the measurement results, the heat treatment in the heat treatment step P3 is carried out at 250° C. or less.

[0153] This heat treatment process completes the production of the electrical resistance material 10. Therefore, in the processes after the mixture film formation process, the mixture 12 is not heated to a temperature exceeding 250° C., and the temperature applied to the mixture 12 is set to 250° C. or less.

[0154] This forms an electrical resistance material 10 having a mixture 12 that contains aluminum and chromium and has a chromium content of 7% by mass or more and 13% by mass or less, and a temperature coefficient of resistance (TCR) of -150 ppm / °C or more and +100 ppm / °C or less.

[0155] Moreover, the electrical resistance material 10 has a volume resistivity (ρ) of 17 [μΩ·cm] or more and 50 [μΩ·cm] or less. [Explanation of symbols]

[0156] 10 Electrical resistance materials 12 mixture 14 Aluminum particles 16 Chromium Particles 18 Dispersion state TCR Temperature Coefficient of Resistance ρ volume resistivity P2 mixture film formation process

Claims

1. An electrical resistance material comprising a mixture containing aluminum and chromium, The mixture is in a dispersed state in which the aluminum and the chromium are not chemically bonded to each other, The chromium content is 7% by mass or more and 13% by mass or less based on the total mass of the mixture, The content of the aluminum is 87% by mass or more and 93% by mass or less based on the total mass of the mixture, The temperature coefficient of resistance is −150 ppm / ° C. or more and +100 ppm / ° C. or less. Electrical resistance material.

2. 2. The electrical resistance material of claim 1 , The mixture does not contain a compound of the aluminum and the chromium. Electrical resistance material.

3. The electrical resistance material according to claim 1 or 2, The volume resistivity is 17 μΩ cm or more and 50 μΩ cm or less. Electrical resistance material.

4. The electrical resistance material according to any one of claims 1 to 3, It is membranous, Electrical resistance material.

5. The electrical resistance material according to any one of claims 1 to 3, The thickness dimension is 100 μm or more in a bulk state. Electrical resistance material.

6. A resistor for current detection, comprising the electrical resistance material according to any one of claims 1 to 5 as a resistor body.

7. forming a mixture containing aluminum and chromium and having a chromium content of 7% by mass or more and 13% by mass or less by sputtering; A method for producing an electrical resistance material, comprising the steps of: applying a temperature to the mixture after formation to no more than 250°C;

8. A method for producing the electrical resistance material according to claim 7, comprising the steps of: The process includes a heat treatment process, In the heat treatment step, the mixture thus formed is heat treated at a temperature of 150° C. or higher and 250° C. or lower.

9. A method for producing the electrical resistance material according to claim 8, comprising the steps of: The heat treatment step includes: A method for producing an electrical resistance material, comprising the steps of: heat treating the material in a nitrogen atmosphere at a temperature between 150° C. and 250° C. for approximately 60 minutes.

Citation Information

Patent Citations

  • The capacitive or resistive thin-film passive element consisting of tantalum alloy aluminum -

    JP1974077174A

  • Production method of highly resistive thin film

    JP1977155397A

  • Chromium-aluminum alloy and thin film element using same

    JP1987077436A

  • Metal thin-film resistor

    JP1988147305A

  • Glazed resistance paste and hybrid integrated circuit device

    JP1990017605A